The potential of self-access language centres in fostering lifelong global citizenship: towards a community of practice approach - Michael D. Smith; Ran Niboshi; Christopher Samuell; Simon F.N. Timms (Quality Education for All)
Purpose – Drawing primarily on the Japanese context, this study aims to highlight this setting to emphasise the potential for tertiary-level self-access language centres to develop lifelong global citizenship, self-reflection and cross-cultural collaboration. Design/methodology/approach – This inquiry calls on the community of practice approach to account for the shared interests motivating lifelong cross-cultural participation, the quality of social engagement between actors, and the material and cognitive tools called upon to realise global citizenship’s shared enterprise. Findings – As argued here, embracing various cultures and inclusive participation can lead to a broader understanding of global citizenship, avoiding narrow-minded views of globalism through shared knowledge and critical practices. Further, self-access provides a cost-effective, technology-mediated alternative to bilateral student mobility, whereby digital community-building occasions cross-cultural practice that may be extended throughout a learner’s life, irrespective of their financial status or place of study. Originality/value – This study is one of a select few drawing on the community of practice framework within the context of lifelong global citizenship. Nevertheless, such an approach remains primed for future development. With a social constructivist philosophy in view, the authors suggest complementary qualitative research approaches that highlight the socially situated nature of both disciplines.